The effect of 30% at-home bleaching on surface hardness of esthetic restorative materials (Mustansiria Dental Journal, 2018)
in vitro study to evaluate the effect of an at-home bleaching product on thesurface hardness of three composite restorative materials.The aim of this study was to evaluate the effect of at-home bleaching on thesurface hardness of the tooth colored restorative materials.Thirty specimens were prepared; 10 specimens of each material 5 specimenscontrol of each group. All specimens were stored in distilled water at roomtemperature for 24 hrs before testing. A universal testing machine (Micromet microhardness testers) was used for testing brinell surface hardness for the three groups&for every tested material. Three tested materials was assessed by ANOVA& furtherexploration between all possible paired combination of tested material was assessedby bonferroni adjusted t-test p value less than 0.05 was considered statisticallysignificant .The statistical analysis showed that at home bleaching technique have statisticallysignificant effect of the micro hardness of composite resin.At-home bleaching agents have a softening effect on some toothcolored restorative material, and the patient must be aware before using them.